2007
DOI: 10.1002/bjs.5817
|View full text |Cite
|
Sign up to set email alerts
|

Autologous tissue repair of large abdominal wall defects

Abstract: Background and method: Techniques for autologous repair of abdominal wall defects that could not be closed primarily are reviewed. Medline and PubMed were searched for English or German publications using the following keywords: components separation technique (CST), Ramirez, da Silva, fascia lata, tensor fasciae latae, latissimus dorsi, rectus femoris, myocutaneous flap, ((auto)dermal) graft, dermoplasty, cutisplasty, hernia, abdominal wall defect, or combinations thereof. Publications were analysed for metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 51 publications
1
70
0
4
Order By: Relevance
“…The aforementioned study demonstrated the lowest recurrence rate in a group undergoing CST hernia repair with soft polypropylene mesh. In the current study, the overall recurrence rate for primary component separation was 20.6%, consistent with other reports [6][7][8][9][10][11]. We were unable to demonstrate a significant difference in hernia recurrence rates between CST alone, CST with biologic mesh or CST with synthetic mesh with a mean follow up of 16 months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The aforementioned study demonstrated the lowest recurrence rate in a group undergoing CST hernia repair with soft polypropylene mesh. In the current study, the overall recurrence rate for primary component separation was 20.6%, consistent with other reports [6][7][8][9][10][11]. We were unable to demonstrate a significant difference in hernia recurrence rates between CST alone, CST with biologic mesh or CST with synthetic mesh with a mean follow up of 16 months.…”
Section: Discussionsupporting
confidence: 89%
“…The technique allows for autologous tissue transfer, approximation of the rectus abdominis muscle complex, and closure of the linea alba following bilateral release of the external oblique aponeurosis and posterior rectus sheath. Recurrence rates with this technique have been reported as low as 18% [7]. While the CST was described without the additional utilization of bioprosthetic meshes, meshes are frequently used an adjunctive reinforcement to a ventral hernia repair.…”
Section: Introductionmentioning
confidence: 99%
“…In Vivo Graft Integration. In order to assess the effects of in vitro incubation periods on tissue integration prospects in vivo, a full thickness segment of the abdominal wall of nude mice, was replaced with muscle grafts of varying degrees of maturity (3,16). All grafts were retrieved and imaged two weeks postimplantation.…”
Section: Resultsmentioning
confidence: 99%
“…angiogenesis | tissue engineering | vascular biology | regenerative medicine F laps serve as important elements in reconstructive surgery, however, the availability of quality autologous muscle flaps, donor site morbidity, length of procedures, and cosmetic concerns present significant limiting factors (1)(2)(3)(4)(5)(6). Tissue survival is dependent on oxygen supply, which is limited to a diffusion distance of up to 300 μm from a supplying blood vessel (7,8).…”
Section: Improved Vascular Organization Enhances Functional Integratimentioning
confidence: 99%
“…Fascia lata graft to repair large abdominal wall defects is resistant and supports intra-abdominal pressures, properly integrating the receiving area (15,16) . Integrated grafts keep the collagen fibers architecture and orientation, and they are easily embedded into the fibrocolagenous tissue without causing foreign body reaction (17) .…”
Section: Introductionmentioning
confidence: 99%